Dawne słowniczki gwarowe jako źródło do historii języka - Nowowiejski, Bogusław (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
Monolingual dictionaries of Polish as well as the old translation dictionaries which until the 19th century also fulfilled the function (in compliance with the intention of their authors) of general Polish dictionaries are traditionally regarded as fundamental sources of the history of the Polish language, especially its development and lexical resources. The collections of folk vocabulary which—more or less professionally—were narrowly used in the papers concerning the past periods of the Polish language aroused poor interest on the part of the historians of language. The article contends that small dialectal dictionaries should be treated equally with other sources of the history of the Polish language, especially lexicographical ones, for they provide a very interesting material for analysis and interpretation, not only linguistic.